2020
DOI: 10.1007/s12134-020-00762-5
|View full text |Cite|
|
Sign up to set email alerts
|

Visualising Immigrant Fertility -- Profiles of Childbearing and their Implications for Migration Research

Abstract: Different measures of fertility have strengths and limitations when used to describe the fertility of immigrants, and no single measure captures every aspect of this complex phenomenon. This paper introduces a novel visual framework that shows life course profiles of immigrant childbearing in a multifaceted way. It develops the well-known cohort fertility curve—showing the average number of children ever born over the life course—and adds lines for immigrant women arriving at different ages, using their averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 78 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Finally, the differences by nativity status within Asian groups may be related to migration effects on fertility, which could lead to the postponement of childbearing until after migration [26]. Prior research has suggested that some immigrant women, depending on their age at migration, have higher fertility compared to their non-immigrant counterparts [27]; especially if these pregnancies are more likely to be intended, immigrants' use of abortion services may be lower than non-immigrants', as found in this analysis. That said, this study does not examine age at migration or fertility desires and further research is needed to assess the influence of tempo or migration effects in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the differences by nativity status within Asian groups may be related to migration effects on fertility, which could lead to the postponement of childbearing until after migration [26]. Prior research has suggested that some immigrant women, depending on their age at migration, have higher fertility compared to their non-immigrant counterparts [27]; especially if these pregnancies are more likely to be intended, immigrants' use of abortion services may be lower than non-immigrants', as found in this analysis. That said, this study does not examine age at migration or fertility desires and further research is needed to assess the influence of tempo or migration effects in this population.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of adaptation from below; in other words, migrants moving from a country with low fertility to one with higher fertility (see Nahmias, 2004, on Former-Soviet Union migrants in Israel; and Tønnessen & Mussino, 2020, on non-family migrants from Germany, Lithuania, and Poland in Norway). The adaptation hypothesis has some shortcomings; for example, for migrants who have more than two children prior to migration it is impossible to adapt to (below) replacement fertility levels in the host country (Adserà et al 2012;Tønnessen & Wilson, 2020), or the birth may be strictly connected to the migration (e.g., Hoem & Nedoluzhko, 2016). These issues can be dealt with, however, by testing the hypothesis across several migrant generations moving from low-to high-fertility countries.…”
Section: Previous Research On Immigrant Fertilitymentioning
confidence: 99%
“…There are various hypotheses used to study immigrant fertility behaviours namely, (childhood) socialisation, adaptation, selection, disruption, interrelation of events and others (Milewski 2010;Tønnessen/Wilson 2020). The fi rst four of these behaviours are the most widely discussed in demography literature.…”
Section: Previous Research and Hypothesesmentioning
confidence: 99%